2022
DOI: 10.3390/biomedicines10030659
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrazolo[3,4-d]Pyrimidine Derivative Si306 Encapsulated into Anti-GD2-Immunoliposomes as Therapeutic Treatment of Neuroblastoma

Abstract: Si306, a pyrazolo[3,4-d]pyrimidine derivative recently identified as promising anticancer agent, has shown favorable in vitro and in vivo activity profile against neuroblastoma (NB) models by acting as a competitive inhibitor of c-Src tyrosine kinase. Nevertheless, Si306 antitumor activity is associated with sub-optimal aqueous solubility, which might hinder its further development. Drug delivery systems were here developed with the aim to overcome this limitation, obtaining suitable formulations for more effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In recent years, we obtained promising results in developing compounds active against GBM by inhibiting Src. Derivative Si306 28a (Figures 7 and 8) is an ATP-competitive small molecule Src inhibitor (K i = 0.13 µM) [147,148] which accommodates into the Src catalytic pocket forming two hydrogen bonds, one between the C4 amino group and the Thr338 OH side chain, and the other one between the N2 of the pyrazolopyrimidine and the NH of Met341 (Figure 8) [147]. Furthermore, SI306 is able to induce apoptosis in patients derived invasive GBM cell lines [149] and in combination with radiotherapy significantly inhibited U87 GBM xenografts growth in nude mice, compared to both control and single treatment [150].…”
Section: Si306 and Analogue Compoundsmentioning
confidence: 99%
“…In recent years, we obtained promising results in developing compounds active against GBM by inhibiting Src. Derivative Si306 28a (Figures 7 and 8) is an ATP-competitive small molecule Src inhibitor (K i = 0.13 µM) [147,148] which accommodates into the Src catalytic pocket forming two hydrogen bonds, one between the C4 amino group and the Thr338 OH side chain, and the other one between the N2 of the pyrazolopyrimidine and the NH of Met341 (Figure 8) [147]. Furthermore, SI306 is able to induce apoptosis in patients derived invasive GBM cell lines [149] and in combination with radiotherapy significantly inhibited U87 GBM xenografts growth in nude mice, compared to both control and single treatment [150].…”
Section: Si306 and Analogue Compoundsmentioning
confidence: 99%
“…Activity screening determined that the newly synthesized tricyclic pyrazole [3,4-d]pyrimidinone derivatives exhibit exceptional anticancer properties. Studies have shown that pyrimidine compounds hold significant potential in the advancement of antitumor drugs [14,15], therefore, they have considerable market prospects and could be further developed as lead compounds [16][17][18][19][20][21][22][23] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%